NRAS mutant melanoma: towards better therapies - Randic, Tijana; Kozar, Ines; Margue, Christiane; Utikal, Jochen; Kreis, Stephanie (Cancer treatment reviews, 2021)
Genetic alterations affecting RAS proteins are commonly found in human cancers. Roughly a fourth of melanoma patients carry activating NRAS mutations, rendering this malignancy particularly challenging to treat. Although the development of targeted as well as immunotherapies led to a substantial improvement in the overall survival of non-NRASmut melanoma patients (e.g. BRAFmut), patients with NRASmut melanomas have an overall poorer prognosis due to the high aggressiveness of RASmut tumors, lack of efficient targeted therapies or rapidly emerging resistance to existing treatments. Understanding how NRAS-driven melanomas develop therapy resistance by maintaining cell cycle progression and survival is crucial to develop more effective and specific treatments for this group of melanoma patients. In this review, we provide an updated summary of currently available therapeutic options for NRASmut melanoma patients with a focus on combined inhibition of MAPK signaling and CDK4/6-driven cell cycle progression and mechanisms of the inevitably developing resistance to these treatments. We conclude with an outlook on the most promising novel therapeutic approaches for melanoma patients with constitutively active NRAS. - Statement of significance - An estimated 75000 patients are affected by NRASmut melanoma each year and these patients still have a shorter progression-free survival than BRAFmut melanomas. Both intrinsic and acquired resistance occur in NRAS-driven melanomas once treated with single or combined targeted therapies involving MAPK and CDK4/6 inhibitors and/or checkpoint inhibiting immunotherapy. Oncolytic viruses, mRNA-based vaccinations, as well as targeted triple-agent therapy are promising alternatives, which could soon contribute to improved progression-free survival of the NRASmut melanoma patient group.
Gesehen am 02.02.2023